Comparative analysis of flue-cured tobacco production costs in santander and huila (colombia) (2012)
Santander and Huila are the largest producers of Flue-cured tobacco in Colombia. They differ in their production systems and, consequently, in their production costs. Costs provide valuable information on the efficiency of resource use, a variable that determines the profitability of the crop. The purpose of this study was to determine and analyze the structure of production costs by department, as well as, their differences and possibilities for reduction. Data for the analysis was obtained from the records of Protabaco and surveys of 50 producers (farms) in the municipalities of Campoalegre and Garzon in Huila, and Capitanejo and Enciso in Santander. The results say the costs of the most important factors of production in both departments are: labor, inputs and services. Huila has higher total costs per hectare than Santander, but similar unit costs. Huila has a higher technological level of production, more capital and greater surface area per crop unit than Santander. Production costs can be reduced by increasing the availability of investment capital, and irrigation water, as well as, more efficient management of fertilization, cultural practices and mechanization of land preparation.